Analisis Parameter Sulfur Dioksida dari Aktivitas Transportasi di Sekitar Industri Pertambangan Nikel: Studi Kasus: Jalan Poros Puuruy-Morosi, Desa Puuruy, Kecamatan Morosi Kabupaten Konawe - Rusliaddin, Rusliaddin; Assiddieq, Moch.; Sumarlin, Sumarlin (Universitas Muhammadiyah Kendari, 2022)
Ambient air pollution outside the outdoor environment comes from moving sources, namely exhaust fumes from incompletely burned vehicles such as motorcycles, gasoline cars, diesel cars, Morosi District is an industrial area that accommodates several large companies engaged in energy and mineral purification, so that these companies will accommodate human resources. In this case, of course, many workers use motorized vehicles to optimize working time. The mobility of workers is a contribution to air pollution, especially air resulting from the use of motorized vehicles known as Sulfur Dioxide (SO2). Efforts to monitor the amount of SO2 need to be carried out considering the impact that will arise in the future.The measurement of SO2 concentration was carried out using a measurement procedure method that refers to SNI 19-7117.10-2005, using Impingger. In the morning, afternoon and evening measurements the concentration of SO2 gas reached 50.60 g/m³, 41.80 60 g/m³, and in the afternoon 72.10 g/m the concentration of SO2 was still safe for life and the environment because it did not exceed the quality standard. which is 150 ug/m³.